2018
DOI: 10.1017/s0022149x18000792
|View full text |Cite
|
Sign up to set email alerts
|

Bulk tank milk ELISA to detect IgG1 prevalence and clustering to determine spatial distribution and risk factors of Fasciola hepatica-infected herds in Mexico

Abstract: Fasciola hepatica is a helminth parasite that causes huge economic losses to the livestock industry worldwide. Fasciolosis is an emerging foodborne zoonotic disease that affects both humans and grazing animals. This study investigated the associations between climatic/environmental factors (derived from satellite data) and management factors affecting the spatial distribution of this liver fluke in cattle herds across different climate zones in three Mexican states. A bulk-tank milk (BTM) IgG1 enzyme-linked im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Traditionally, it has been a serious veterinary health concern in areas with diverse socio-economic scenarios and epidemiological contexts such as Europe (Beesley et al ., 2018), East Africa (Gryseels, 1988), South Asia (Gupta and Singh, 2002) and the Bolivian Altiplano (Ueno et al ., 1975). Moreover, increasing trends in the prevalence and/or spreading of animal fasciolosis are presumed at a global scale; in the Americas and the Caribbean (Rojas et al ., 2010; Molento et al ., 2018; Villa-Mancera and Reynoso-Palomar, 2019), in Europe (Pritchard et al ., 2005; Caminade et al ., 2015), in Africa (Jajaa et al ., 2017), in Asia (Nguyen et al ., 2017; Meshgi et al ., 2019) and in Australia and Oceania (Haydock et al ., 2016; Kelley et al ., 2020).…”
Section: Fasciolosis (Re-)emergence: An Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Traditionally, it has been a serious veterinary health concern in areas with diverse socio-economic scenarios and epidemiological contexts such as Europe (Beesley et al ., 2018), East Africa (Gryseels, 1988), South Asia (Gupta and Singh, 2002) and the Bolivian Altiplano (Ueno et al ., 1975). Moreover, increasing trends in the prevalence and/or spreading of animal fasciolosis are presumed at a global scale; in the Americas and the Caribbean (Rojas et al ., 2010; Molento et al ., 2018; Villa-Mancera and Reynoso-Palomar, 2019), in Europe (Pritchard et al ., 2005; Caminade et al ., 2015), in Africa (Jajaa et al ., 2017), in Asia (Nguyen et al ., 2017; Meshgi et al ., 2019) and in Australia and Oceania (Haydock et al ., 2016; Kelley et al ., 2020).…”
Section: Fasciolosis (Re-)emergence: An Overviewmentioning
confidence: 99%
“…Aside from livestock movements, other factors and management activities are highlighted as significant risk-increasing factors: (i) using unsafe water resources and prolonged grazing (for review, see Sabourin et al ., 2018); (ii) feeding on wetland pastures vs feeding on forage/dry-land crop residues (Suon et al ., 2006; Khan et al ., 2009; Takeuchi-Storm et al ., 2017); (iii) increased proportion of grazed grass and length of grazing season (Bennema et al ., 2011); (iv) mixed farming of small and large ruminants; and (v) the use of stagnant pond bathing and river/canal bathing vs river/tap water bathing (Khan et al ., 2009). In some cases, lower levels of literacy of farmers have been associated with higher infection risk, as proper knowledge and comprehension of control strategies in relation to the parasite cycle are essential for decreasing transmission in high-risk areas (Villa-Mancera and Reynoso-Palomar, 2019). Current trends have also led to an increase and expansion of organic ruminant production.…”
Section: Social Factors: Human Behaviour As Ultimate Driver Of Fasciomentioning
confidence: 99%
See 2 more Smart Citations
“…In Mexico, several recent studies using bulk-tank milk enzyme-linked immune sorbent assay (ELISA) in cattle herds have indicated that the F . hepatica prevalence in three climate regions ranged from 62.76% to 63.56% (Villa-Mancera & Reynoso-Palomar, 2019a, b). A high prevalence of parasite infection in cattle has been found in north-west Mexico using the indirect ELISA test (24.4%) and sedimentation faecal examination (11.4%) (Munguía-Xóchihua et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%